LaboratOry for the Behavior of the SloT Region: a small mission doing big radiation science - Filwett, Rachael; Miles , David; Jaynes , Allison; Gabrielse, Christine (Frontiers in Astronomy and Space Sciences, 2025)
This paper outlines the science and basic design choices associated with a mission concept study known as the LaboratOry for the Behavior of the SloT Region (LOBSTR). This mission concept focuses on energetic particles, both electrons and protons, as they impinge upon the slot region in the Van Allen radiation belts around Earth. In particular, it emphasizes the drift dynamics of particles that were not captured by Van Allen Probes. We conceptualize a mission, utilizing state-of-the-art instruments and components, and calculate the mission’s orbit, thrust, and radiation requirements using industry-standard methods. The concept uses two SmallSats in a near-equatorial orbit, with precise orbital timing to capture the desired dynamics. The total radiation dose and the details of the orbital dynamics are examined and found to be within the capabilities of current technology.